Landscape Composition and Spatial Prediction of Alveolar Echinococcosis in Southern Ningxia, China - Pleydell, David R. J.; Yang, Yu Rong; Danson, F. Mark; Raoul, Francis; Craig, Philip S.; McManus, Donald P.; Vuitton, Dominique A.; Wang, Qian; Giraudoux, Patrick (PLOS Neglected Tropical Diseases, 2008)
Author Summary In humans, larvae of the fox tapeworm Echinococcus multilocularis typically infect the liver where metastasis, calcification and necrosis cause the zoonotic disease alveolar echinococcosis (AE). Treatment is difficult. Early detection greatly increases patient life expectancy but under-detection is a problem. Understanding the ecological conditions that elevate AE risk would help identify at-risk communities. Voles and lemmings of the subfamily Arvicolinae are important intermediate hosts in most AE endemic areas, and arvicoline habitat has been proposed as a predictor of AE risk. Using a model of spatial autocorrelation with land cover identified from satellite remote sensing imagery, we identified AE hotspots in southern Ningxia Hui Autonomous Region (NHAR), China. Hotspots were not located near optimal arvicoline habitats. Thus, non-arvicolines provide principal reservoirs in NHAR and the range of ecological conditions sustaining E. multilocularis transmission in China is greater than previously thought. We also show: social factors explain higher prevalence in females than males; dogs increase infection risk; and we argue that water source quality is important via interaction with other environmental variables. Our map of AE prevalence represents the current state-of-the-art regarding the spatial distribution of AE in southern NHAR and provides an important baseline for future monitoring programs there.